Synthesis of the E ring of salinomycin : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Edmonds, Michael Kevin; Edmonds, Michael Kevin (Massey University, 1995)
The synthesis of (2R*, 5R*, 2'S*) and (2S*, 5R*, 2'S*)-2-(iodomethyl)-5-(2'-methyltetrahydrofur-2'-yl)tetrahydrofurans 331a, 331b in a 5:1 ratio by the iodoetherification of (1R*, 2'S*)-1-(2'-methyltetrahydrofur-2'-yl)-4-penten-1-ol 330a is described. Subsequent iodoetherification of ether derivatives 385 - 389 of hydroxyalkene 330a was then effected to produce predominantly the cis iodide 331b. (1R*, 2'S*)-1-(2'-methyltetrahydrofur-2'-yl)-1-(2", 6"-dichlorobenzyloxy)-4-pentene 387 proved most successful in this respect affording iodides 331a, 331b in a 1:10 ratio. Attempted silver catalysed ring expansion of iodide 331a proved ineffective affording only (5R*, 2'S*)-5-(2'-methyltetrahydro-2'-yl)-5-hydroxypentan-2-one 344. The synthesis of (E)-1-bromo-3-ethyl-3-pentene 146 is described, the key step in its formation being the diastereoselective reaction of 2-ethyl-1-butene 364 with butyl glyoxylate 367, in the presence of a titanium catalyst formed in situ from diisopropoxytitanium(VI) dichloride 362 and (±)-1,1'-bi-2-naphthol 363, to afford butyl (E)-4-ethyl-2-hydroxy-4-hexenoate 370. The synthesis of (2S*, 3R*, 6R*, 2'S*)-3-ethyl-3-hydroxy-2-methyl-6-(2'-methyltetrahydrofur-2'-yl)tetrahydropyran 323 from 2-methyl-2-tetrahydrofuraldehyde 322 is described, thereby modelling the synthesis of the E ring of salinomycin. The synthesis began with the coupling of the organolithium derivative of (E)-1-bromo-3-ethyl-3-pentene 146 to 2-methyl-2-tetrahydrofuraldehyde 322 to afford (4E, 1R*, 2'S*)- and (4E, 1S*, 2'S*)-4-ethyl-1-(2'-methyltetrahydrofur-2'-yl)-4-hexen-1-ol 348a, 348b in a 3:1 ratio. Following separation of the alcohols 348a, 348b via formation of their acetate derivatives 383a, 383b, iodoetherification of (4E, 1R*, 2'S*)-4-ethyl-1-(2'-methyltetrahydrofur-2'-yl)-4-hexen-1-ol 348a afforded (2R*, 5R*, 1'S*, 2"S*)- and (2S*, 5R*, 1'R*, 2"S*)-2-ethyl-2-(1'-iodoethyl)-5-(2"-methyltetrahydrofur-2"-yl)tetrahydrofurans 347a and 347b in a 3:1 ratio. Subsequent ring expansion of iodide 347b resulted in formation of the target pyran 323 in 77% yield. Iodoetherification of the trimethylsilyl derivative 392 of (4E, 1R*, 2'S*)-4-ethyl-1-(2'-methyltetrahydrofur-2'-yl)-4-hexen-1-ol 348a produced the iodides 347a and 347b in a 1:1 ratio, while the 2,6-dichlorobenzyl 390 and 4-bromobenzyl 391 derivatives were too sterically hindered for iodoetherification to occur.
Keywords: Salinomycin; Antibiotics